Trimethoprim/sulfamethoxazole versus vancomycin in the treatment of healthcare/ventilator-associated MRSA pneumonia: a case–control study. (19th December 2016) - Eliakim-Raz, Noa; Hellerman, Moran; Yahav, Dafna; Cohen, Jonathan; Margalit, Ili; Fisher, Sharon; Zusman, Oren; Shaked, Hila; Bishara, Jihad
Abstract : Objectives: Therapeutic options available to treat MRSA pneumonia are limited. Trimethoprim/sulfamethoxazole is an attractive treatment because of its bactericidal anti-MRSA activity, oral and parenteral formulations and good penetration to the lung tissue. We aimed to compare the efficacy and safety of trimethoprim/sulfamethoxazole with vancomycin in the treatment of healthcare/ventilator-associated MRSA pneumonia. Methods: We carried out a retrospective case–control study of all consecutive hospitalized adult patients diagnosed with MRSA pneumonia at Beilinson Hospital during 2010–15 and treated with either vancomycin or trimethoprim/sulfamethoxazole. The primary outcomes were all-cause mortality at 30 days and clinical failure at the end of treatment. In order to reduce bias affecting the decision to use a specific antibiotic and as a sensitivity analysis, a propensity-score model for choosing between vancomycin and trimethoprim/sulfamethoxazole was used. Results: We identified 42 patients with MRSA pneumonia treated with trimethoprim/sulfamethoxazole and 39 treated with vancomycin. There were no significant differences in the baseline characteristics between the groups. Vancomycin-treated patients showed significantly higher 30 day mortality on both multivariate analysis (HR = 5.28; 95% CI = 1.50–18.60; P  < 0.05) and sensitivity analysis with propensity score [vancomycin 13/24 (54.1%) versus trimethoprim/sulfamethoxazole 4/24 (16.7%); P  < 0.05], and higher clinical failure rates [vancomycin 23/39 (59%) versus trimethoprim/sulfamethoxazole 15/42 (35.7%); P  < 0.05], also in the sensitivity analysis with propensity score [vancomycin 14/24 (58.3%) versus trimethoprim/sulfamethoxazole 6/24 (25%); P  < 0.05]. The rates of side effects in both arms were comparable. Conclusions: Trimethoprim/sulfamethoxazole appears to be superior to vancomycin in the treatment of MRSA pneumonia. A large-scale randomized controlled trial is needed to evaluate these findings.